Rational and emotional components of attitude to the disease in patients with type 1 diabetes: relationship with psychological well-being - Oleg Gennad'evich Motovilin; Yulia Andreevna Shishkova; Elena Viktorovna Surkova (Сахарный диабет)
Aim. To study the relationship between two components of the attitude (rational and emotional) of patients with type 1 diabetes (T1D) to the disease among themselves as well as the relationship of each component with psychological well-being of patients. Materials and methods. One hundred twenty-nine T1D patients (43 males, 86 females) were studied. The attitude towards the disease was studied using the Colour Attitude Test (CAT) by A.M. Etkind and the Psychological Diagnosis of the Type of Person?s Attitude to the Disease (TAD) developed at the Bekhterev Psychoneurological Research Institute (St. Petersburg). Psychological well-being was evaluated using the 36-item Short-Form Health Survey (SF-36), the State?Trait Anxiety Inventory (STAI) by C.D. Spielberger that was adapted by Y.L. Khanin, the Centre for Epidemiological Studies Depression Scale (CES-D), the self-assessment diagnostic technique by Dembo?Rubinstein and the Purpose in Life Test (PILT) by Crumbaugh & Maholick that was adapted by D. Leontyev. Results. There were two groups of patients in the results of cluster analysis of TAD: those with rational adaptive and maladaptive attitudes towards the disease. In the group of patients with the rational adaptive attitude towards the disease, scores were higher on most scales of STAI, CES-D, SF-36 and PILT. In the result of cluster analysis of CAT, there were two groups of patients: those with favourable and unfavourable emotional acceptance of the disease. The group of patients with favourable emotional acceptance of the disease also had higher scores on most scales of STAI, CES-D, SF-36, PILT and the Dembo?Rubinstein technique. The comparative analysis of the relationship of rational and emotional components in attitude to the disease showed their incomplete coincidence among themselves. Conclusions. Both the rational and emotional components of the attitude towards the disease are associated with the psychological well-being of patients. Patients with the adaptive rational attitude towards the disease and a high level of emotional acceptance are characterised by a high level of psychological well-being.